Resource Curse In Reverse: The Coffee Crisis And Armed Conflict In Colombia (2006)
Between 1998 and 2003 production increases in Brazil and Vietnam drove down the price of coffee by 73 percent in global markets, triggering the ¿international coffee crisis¿. We examine the effect of this exogenous price shock on Colombia¿s civil war, exploring whether politically-motivated violence presented different dynamics in the coffee -growing regions relative to the non- coffee regions, during the pre-crisis and crisis periods. Using a difference-in-differences framework, we find causal evidence that the steep decline in coffee prices substantially increased both the incidence and intensity of Colombia¿s civil war. We also propose a simple model linking the price shock to violence and empirically examine the relative importance of three potential mechanisms. While crop substitution from coffee to coca explains very little of the variation, a disproportionate increase in poverty in coffee areas is associated with greater violence, as is a lower state capacity.